CFD simulation of hydrodynamics in spray dryer - Siti Ferdaus, Aspari (2010)
Spray dryer is a well established method for converting liquid feed materials into dry powder forms. Spray dryer is widely used to produce foods such as whey,instant drinks, milk, tea and soups, as well as healthcare and pharmaceutical products, such as vitamins, enzymes, bacteria and also in production of fertilizers, detergent soap, and dyestuffs. Many experimental studies have been done to ensure the quality of the spray drying process. Alternatively, computational fluid dynamics (CFD) can be utilized to study the performance of the spray dryer. CFD modelling tools are increasingly used in the design, scale up, optimization and trouble-shooting of the spray drying chamber because measurements such as Laser Droppler Anemometer (LDA) of air flow, temperature, particle size and humidity within the drying chamber are very difficult and expensive in a large scale spray dryer. Hydrodynamics of the spray dryer in single and multiphase flow are not well understood and hence for economic and safety reasons, reliable models are needed for scale-up and design of such a spray dryer. In this work, a CFD modelling of hydrodynamics in counter-current and co-current spray drying tower were performed. The turbulence modelling was realized using five different turbulent models, i.e. standard k-ε, RNG k-ε, Realizable k-ε, Reynolds stress models and the Detached Eddy Simulation. The predicted airflow patterns inside the spray drying chamber were found to be in good agreement to the experimental data adopted from literature for all turbulence models tested in this work. A great potential of the Detached Eddy Simulation for predicting the flow pattern in counter-current and cocurrent spray dryer were uncovered as its provides more accurate predictions compared to other models tested in this work. Results from this simulation may be useful for development of a more comprehensive and accurate model for spray dryer in the future.